PENGARUH PENGGUNAAN MEDIA VIDEO TUTORIAL DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR SENI BUDAYA SUB SENI RUPA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 25 PADANG - Wella Oktarina, Dr. Ramalis Hakim, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this research is to know the learning outcomes of students which teach with tutorial video and without tutorial video. Whether students with high prior knowledge or low prior knowledge  the result of this research showed that the post-test value “ Seni Rupa “ skill and knowledge  eksperiment class and control class 78.33, 74,67 and 87.33, 73.00 value of t-count 5.047 >   t-table, there is influence of using tutorial video and prior knowledge to the result of learning “ Seni  Rupa “Keywors : tutorial video and Learning Outcomes